2018
DOI: 10.4997/jrcpe.2018.115
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Physical Fitness Training for Stroke Survivors

Abstract: Background Physical tness is impaired after stroke, yet tness training after stroke reduces disability. Several international guidelines recommend that tness training be incorporated as part of stroke rehabilitation. However, information about cost-effectiveness is limited.Methods A decision tree model was used to estimate the cost-effectiveness of a tness programme for stroke survivors vs. relaxation (control group). This was based on a published randomised controlled trial, from which evidence about quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…The AEX + TST also improved their cardiorespiratory fitness more than the TST group, which is an important risk factor in the prevention of stroke (Hussain et al, ; Pandey et al, ). These findings support the merit of including aerobic exercise as part of a comprehensive stroke rehabilitation intervention (Collins, Clifton, Wijck, & Mead, ; Gezer, Karaahmet, Gurcay, Dulgeroglu, & Cakci, ).…”
Section: Discussionsupporting
confidence: 71%
“…The AEX + TST also improved their cardiorespiratory fitness more than the TST group, which is an important risk factor in the prevention of stroke (Hussain et al, ; Pandey et al, ). These findings support the merit of including aerobic exercise as part of a comprehensive stroke rehabilitation intervention (Collins, Clifton, Wijck, & Mead, ; Gezer, Karaahmet, Gurcay, Dulgeroglu, & Cakci, ).…”
Section: Discussionsupporting
confidence: 71%
“…Nonetheless, we seek to advocate for patients and challenge payers by presenting scientific evidence that exercise is not only good for one's health but can facilitate brain function and potentially reduce disability. 18,55 Figure 2. Line plot depicting means and SDs of Fugl-Meyer scores at baseline, EOT, and EOT+4.…”
Section: Considerations For Clinical Translationmentioning
confidence: 99%
“…Importantly, none of the studies included any measure of costs. A recent study demonstrated the cost‐effectiveness (Collins, Clifton, van Wijck, & Mead, ) of a clinically effective community‐based fitness training program for ambulatory stroke survivors (Mead et al., ), but more health‐economic evidence is required for service development.…”
Section: Discussionmentioning
confidence: 99%